Mapping molecular function to biological nanostructure: Combining structured illumination microscopy with fluorescence lifetime imaging - Görlitz,F; Corcoran,DS; Sparks,H; Leitinger,B; Neil,M; Dunsby,C; French,P (2017)
We report the enhancement of spatial resolution and sensitivity of wide-field time-gated imaging and the combination with SIM to map molecular function using FRET to biological nanostructure below the conventional diffraction limit.